Diverticulitis: a comprehensive review with usual and unusual complications - Onur, Mehmet Ruhi (Insights Imaging, 2016)
ABSTRACT: Diverticulitis is characterized by inflammation of the outpouchings of the bowel wall. Imaging findings of diverticulitis include edematous thickening of the bowel wall with inflammatory changes within the adjacent mesenteric fat. Uncomplicated diverticulitis can be treated conservatively; however, complicated diverticulitis may not be responsive to medical treatment and life-threatening conditions may occur. In this review, we aimed to illustrate the ultrasonography (US) and computed tomography (CT) features of diverticulitis and its complications including perforation, phlegmon, abscess, ascending septic thrombophlebitis (phylephlebitis), bleeding, intestinal obstruction, and fistula. TEACHING POINTS: • Complications of diverticulitis may be highly variable. • It may be difficult to diagnose diverticulitis as underlying cause of severe complications. • MDCT is essential for the primary diagnosis of the acute diverticulitis and its complications.